Russian young people’s subjective health evaluations, self-care practices, and therapeutic networks - Mikhaylova, Oxana (Frontiers in Psychology, 2024)
This study investigates the relationship between young people's subjective health evaluations, selfcare practices, and therapeutic networks using semi-structured interviews and the computerized qualitative thematic analysis capabilities of the MAXQDA software. In the summer of 2022, 41 Russian youths, ages 16 to 25, took part in this investigation. The major findings demonstrate that young people who had low health evaluations were more likely to conduct self-care with the intention of enhancing their health and to have mothers and other medical experts in their therapeutic networks. Furthermore, individuals who claimed that their health was inadequate engaged in more sports and took care of themselves even when they were ill. There was no association between the objectives of self-care practices, members of the therapeutic network, and self-care activities in terms of the type of health evaluation. Overall, it is possible to suggest that the practices and the structure of therapeutic networks are related to self-evaluated health, but quantitative study is needed to verify the causal relationship.